IMPLEMENTASI PROGRAM CORPORATE SOCIAL RESPONSIBILITY PERSEROAN TERBATAS PERTAMINA HULU ENERGI NSB & NSO DI DESA RAYEUK MEUNYE, KECAMATAN TANAH LUAS, KABUPATEN ACEH UTARA - Raina Safina; Februati Trimurni (Transpublika Publisher, 2022)
long-term economic development in order to improve the quantity and quality of life in the society surrounding it. The goal of this research is to describe the execution of PT. Pertamina Hulu Energi NSB & NSO's CSR program in Rayeuk Meunye Village, Tanah Luas District, North Aceh Regency, with the program's target community being the Rayeuk Meunye Village Community. In this study, a descriptive method with a qualitative approach was used, and data was collected through observation, interviews, and recording. The general head of PT. Pertamina, the Head of Public Relations of PT. Pertamina, public relations staff/employees, and the Rayeuk Meunye village community were the ten informants involved for this study. Data analysis technique consisting of three stages: data reduction, data display, and conclusion drafting. The findings of this study reveal that PT. Pertamina Hulu Energi NSB & NSO's CSR initiative in the form of cocoa planting is ineffective since not all community members are targeted. Furthermore, the benefits perceived by the community have not been dispersed equitably because some people do not focus on operating the program. As such, the desired change is discovered, not everyone feels the change with the program since there are still people who do not collaborate in running the program, they set it aside and consider this cocoa cultivation program is a side job.